Hak Waris Anak dalam Kandungan (Studi Komparatif Mazhab Syāfi’i dan Mazhab Hanafi) - Akhmad Hanafi Dain Yunta; Chamdar Nur; Amirullah Amirullah (BUSTANUL FUQAHA: Jurnal Bidang Hukum Islam, 2022)
This study aims to determine the determination of the inheritance rights of children in the womb by comparing the Syafii school of thought and the Hanafi school of thought. This study uses a type of library research (Library Research), which seeks data through existing literature, as well as draws conclusions as answers to the problems that have been formulated. The results showed that the determination of the inheritance rights of the child in the womb according to the Syafii school of thought is the distribution of inheritance in the al-ḥaml case, it should be postponed until the fetus in the womb is born, so that the situation becomes clear. The Hanafi school of thought says that the division of the inheritance of children in the womb can be distributed without having to wait for the birth of the fetus.